Epidemiology of dengue and dengue haemorrhagic fever in Malaysia. III. A comparative study of clinical features seen in virologically confirmed cases for periods between 1963-1987--a review. - Shekhar, K.C.; Senan, P. (1992)
Dengue fever, Dengue hemorrhagic fever and Dengue shock syndrome within the dengue complex is a sinister disease of great public health importance and continues to ravage children, young adults and the aged in Malaysia. The history of the disease is traced for over the years and the changing pattern of clinical presentation are noted. Various hospital based studies have been compared and the pathognomonic features of the disease in Malaysia are highlighted.